Faculty of Nursing on the Move. - Boschma, Geertje (University Of Calgary Press, 2005)
This book provides a historical analysis of the Faculty of Nursing at the University of Calgary in contrast and comparison to the broader evolution of academic nursing in Canada. It addresses how the faculty has responded to important social trends and changes in health care policy and helps the reader to understand contemporary nursing issues. Starting with the dramatic changes in health care policy after the Second World War, it establishes the role of nursing education as pivotal to a growing health care industry. The book then moves on to describe the challenge of developing an identity for an academic unit within the larger academic and health care structure. This book will be of particular interest to anyone involved in women's studies as it represents a case study for broader women's issues within an academic environment.